1994
DOI: 10.1115/1.2911450
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Microscale Conductive and Radiative Heat Transfer

Abstract: This work addresses challenges in the emerging field of microlength scale radiative and conductive heat transfer in solids and recommends specific directions of future research. Microlength scale heat transfer involves thermal energy transport processes in which heat carrier characteristic lengths become comparable to each other or the characteristic device dimension. Identification of these characteristic lengths leads to the definition of different microscale heat transfer regimes. A review of the theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(56 citation statements)
references
References 44 publications
(62 reference statements)
0
56
0
Order By: Relevance
“…This is actually not surprising because d is, in addition to the wavelength, the relevant length scale for the propagation of electromagnetic waves inside the material. Therefore, it is physically sound that the induced currents, and thus the field close to the surface, be correlated over a distance which is the smallest of d and l. This result, which, to our knowledge, was never pointed out before, has important consequences in the modeling of radiative transfer at small scales [3,4]. Moreover, it allows us to revisit the concept of emissivity at subwavelength scale, useful in the study of the radiative properties of rough surfaces [12].…”
Section: Rémi Carminati and Jean-jacques Greffetmentioning
confidence: 79%
See 1 more Smart Citation
“…This is actually not surprising because d is, in addition to the wavelength, the relevant length scale for the propagation of electromagnetic waves inside the material. Therefore, it is physically sound that the induced currents, and thus the field close to the surface, be correlated over a distance which is the smallest of d and l. This result, which, to our knowledge, was never pointed out before, has important consequences in the modeling of radiative transfer at small scales [3,4]. Moreover, it allows us to revisit the concept of emissivity at subwavelength scale, useful in the study of the radiative properties of rough surfaces [12].…”
Section: Rémi Carminati and Jean-jacques Greffetmentioning
confidence: 79%
“…Nevertheless, recent interest in microscale and nanoscale radiative transfers [3], together with the development of local-probe thermal microscopy [4] and the observation of coherent thermal emission from doped silicon and silicon carbide (SiC) gratings [5,6], has raised new challenges. In fact, all these topics have in common the substantial role of the nonradiating (evanescent) thermal fields.…”
Section: Rémi Carminati and Jean-jacques Greffetmentioning
confidence: 99%
“…Thermal properties of semiconductor superlattices have been under intense investigation due to their potential uses in thermoelectric energy conversion [1][2][3] and optoelectronic devices [4]. The thermal conductivity of superlattices can be even lower than their alloy counterparts [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…To the macro level to explain these issues, a comprehensive and integrated film thermal conductivity model should take into account The anisotropy of the material, the nonuniformity of the material, and the temperature dependence of the membrane material. [41] In view of the differences in the results of many experiments, Tien and Chen [20] put forward a valuable idea, that is, the different laboratories that are engaged in thin film thermal conductivity measurements should be tested against the same batch of samples provided by the same supplier to assess the accuracy and reliability of the methods used and to have a true characteristic of the thermal conductivity of the film complete understanding. Correspondingly, the flow and radiation problem is also necessary to adopt similar research strategy.…”
Section: Micro Devices Heat Transfer Problems Arise Scale Effect and mentioning
confidence: 99%
“…All this is closely related with the practical application, for example, due to the rapid development of low-temperature technology and thin metal film and metal wire application growth needs, Tien et al [ 10] on the thin metal film and metal lines were calculated and found that its conductivity and thermal conductivity are lower than the corresponding value in the macroscopic case, one of the reasons is close to the surface of the average free electrons due to the interface of the scattering will be shortened, and the electron mean free path increases with the decrease of temperature, especially at low temperature, when the average free path of energy carrier (such as electron) is the smallest of the given sample In the order of magnitude, the transport of these carriers will reflect the dependence on the size of the sample [11], resulting in the traditional theory of the predicted physical properties of the sample and its real value there is a significant deviation, it is these theories and experiments the observed contradictions contribute to the development of micro-scale thermal science. Micro-scale heat transfer and fluid science cover a very broad field [12][13][14][15][16][17][18][19][20], such as solid-liquid films, semiconductor devices, optical devices, superconducting devices, chip cooling devices, micro-electromechanical systems, biochips, microsensors, laser processing, thermal medical engineering, life and thermal science and contains a lot of challenging topics.…”
Section: Micron/nano Scale Thermal Science and Engineering Developmentmentioning
confidence: 99%